Cost Structure of Conventional Steam Heated Timber Kiln Drying Industry in Malaysia - Ayeru, A. Singaram (2002)
Steam heated kiln drying is one the of the method used for drying timber. This activity involves the establishment of kiln plants which requires large capital investment. The economics of kiln drying operation is important in order to determine the optimal level of timber to be dried. This can be estimated through understanding the cost structure and cost function of the industry. A study was conducted to estimate the cost structure of steam-heated wood drying activities. Data on cost and other associated information on production of kiln drying activities as well as background information of the firm were collected through personal interview. A structured questionnaire was used to collect information required in the study. A total of 104 kiln plants, which are currently operated in Malaysia, were interviewed. Data were analysed to obtain the average cost of drying timber and statistical analysis was carried out to test the mean differences between plants size. An empirical analysis was conducted to estimate the cost function of the industry.